Pembelajaran Inkuiri Terbimbing untuk Melatih Kreativitas dan Keterampilan Berpikir Ilmiah Siswa (UPEJ Unnes Physics Education Journal, 2019)
This research aims to analyze the creativity and students' scientific thinking skills in guided inquiry learning. This research is a pre-experimental research design type One-Shot Case Study. Sampling was done by purposive sampling technique. Data collection methods used are observation and questionnaire methods. The instruments used in this study were creative attitude questionnaires, project product creativity assessment sheets, and scientific thinking skills assessment sheets. Data analysis was performed using a percentage formula. The results show that students 'creativity included in the high category and students' scientific thinking skills included in good category